Axons of retinal ganglion cells on the optic nerve disc following vessel density correction at different IOP values - Lešták, Ján; Fůs, Martin; Král, Jakub (Experimental and therapeutic medicine, 2023)
The present study aimed to determine how the vascular density (VD) in each segment peripapillary influences the retinal nerve fiber layer (RNFL) and to eliminate its contribution to RNFL in pathological intraocular pressure (IOP). In a cohort of 69 subjects (mean age, 45±6 years old) with untreated ocular hypertension (122 eyes in total) enrolled in this study, Ocular Response Analyser IOP was measured during routine outpatient care. Its value was >21 (range, 21-36) mmHg in all eyes. Furthermore, peripapillary VD and RNFL were measured using optical coherence tomography in the following eight segments: Inferior temporal (segment 1); temporal inferior (segment 2); temporal superior (segment 3); superior temporal (segment 4); superior nasal (segment 5); nasal superior (segment 6); nasal inferior (segment 7); and inferior nasal (segment 8). The visual field examination was performed with the fast threshold glaucoma program using the Medmont M 700. The overall defect was evaluated. Person's correlation coefficient was used to assess the correlation between VD and IOP. The largest changes were observed in peripapillary segments 1, 4, 5, 6, 7 and 8. The second part of the work was to eliminate the contribution of VD to RNFL. The partial correlation coefficient r was used to adjust RNFL from VD to assess the dependence between the selected parameters. The largest changes in RNFL were in segments 5 and 8 after they had been 'cleaned' of peripapillary VD. In conclusion, the present study revealed that the largest changes in RNFL after VD adjustment were observed for the incipient hypertensive glaucoma in segments 5 and 8.
Keywords: intraocular pressure; optical coherence tomography with angiography; ocular hypertension; vessel density; retinal nerve fiber layer